2022
DOI: 10.3390/ma15062012
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Antibacterial Activity of EndoSeal MTA, iRoot SP, and AH Plus against Planktonic Bacteria

Abstract: This study aimed to investigate the antibacterial activity of three endodontic sealers, AH Plus, iRoot SP, and EndoSeal MTA, against four planktonic bacteria species. The antibacterial activity of the three endodontic sealers was assessed using a modified direct contact test. Bacteria suspension of Actinomycoses viscosus, Enterococcus faecalis, Staphylococcus aureus, and Streptococcus mutans were left in contact with the sealers that were pre-set or set for 1, 3, 7, and l4 days for an hour. Freshly mixed AH Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Related to AH Plus, its antimicrobial activity was previously demonstrated [39], and more recently Mak et al have shown that although this sealer has a strong antimicrobial activity when freshly prepared (from the formaldehyde released during the polymerization process), it decreases after time [40], which could be related with the low solubility of this sealer.…”
Section: Discussionmentioning
confidence: 98%
“…Related to AH Plus, its antimicrobial activity was previously demonstrated [39], and more recently Mak et al have shown that although this sealer has a strong antimicrobial activity when freshly prepared (from the formaldehyde released during the polymerization process), it decreases after time [40], which could be related with the low solubility of this sealer.…”
Section: Discussionmentioning
confidence: 98%
“…suggested that the reduced cell viability may be linked to both the epoxy resin and the amines. [ 24 ] Epoxy resin-containing sealers have been evaluated for their cytotoxic properties, primarily because of their component bisphenol (diglycidyl ether), which is recognized for its mutagenic characteristics. [ 10 ] Among all the sealers tested, AH Plus consistently exhibited the least cell viability throughout all the experimental time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ADT was used, and one of the disadvantages of this test is that it does not distinguish between bactericidal properties. The lack of standardization in inoculum density, culture media, sample size, number of specimens per plate, storage conditions, agar viscosity, temperature, and incubation duration can significantly impact the assessment of endodontic sealers' antibacterial effectiveness [14,15]. These parameters should be standardized and integrated to obtain more conclusive results and minimize the influence of in vivo variations.…”
Section: Discussionmentioning
confidence: 99%